Data-driven discovery of high-performance multicomponent solid solution thermoelectric materials. (August 2022) - Zhang, Zixun; Chen, Heyang; Wei, Tian-Ran; Zhao, Kunpeng; Shi, Xun
Abstract: The discovery and exploration of novel thermoelectric materials over the past decades have relied primarily on the inefficient Edisonian trial and error approach. It is urgent to develop intelligent approaches like machine learning or data-driven screening to accelerate the process of discovery and optimization of high-performance thermoelectric materials. In this study, by taking the Cu2 (S, Se, Te) solid solutions as an example, we demonstrate a successful data-driven screening approach to reveal the optimal composition ranges with high thermoelectric performance. Based on the known experimental data of Cu2 (S, Se, Te) and their solid solutions, we predicted the contouring diagrams of crystal structures and thermoelectric properties of Cu2 (S, Se, Te) multicomponent materials. Following the prediction, we fabricated a series of Cu2 (S, Se, Te) quaternary solid solutions and systematically investigated their crystal structures, phase transitions, and especially thermoelectric properties. A peak zT of 1.3 at 1000 K is achieved in Cu2 S0.4 Se0.3 Te0.3, which is well in the predicted optimal composition range. We expect this simple yet efficient strategy to be widely applied to the quick screening of other high-performance thermoelectric materials. Graphical abstract: By taking the Cu2 (S, Se, Te) solid solutions as an example, we demonstrate a successful data-driven screening approach to reveal the optimal composition ranges with high thermoelectric performance. Image 1 Highlights: An effective data-driven screening approach was proposed to discover high-performance thermoelectric materials. The crystal structures and thermoelectric properties of Cu2 (S, Se, Te) were comprehensively investigated. The optimal composition range was revealed for Cu2 (S, Se, Te) material system.